Tools and algorithms for the construction and analysis of systems : 22nd International Conference, TACAS 2016, held as part of the European Joint Conferences on Theory and Practice of Software, ETAPS 2016, Eindhoven, Netherlands, April 2-8, 2016. Proceedings /: 22nd International Conference, TACAS 2016, held as part of the European Joint Conferences on Theory and Practice of Software, ETAPS 2016, Eindhoven, Netherlands, April 2-8, 2016. Proceedings. (2016) - Unknown
No abstract available